2000
DOI: 10.1098/rspb.2000.1011
|View full text |Cite
|
Sign up to set email alerts
|

Extreme environmental change and evolution: stress-induced morphological variation is strongly concordant with patterns of evolutionary divergence in shrew mandibles

Abstract: Morphological structures often consist of simpler traits which can be viewed as either integrated (e.g. correlated due to functional interdependency) or non-integrated (e.g. functionally independent) traits. The combination of a long-term stabilizing selection on the entire structure with a short-term directional selection on an adaptively important subset of traits should result in long historical persistence of integrated functional complexes, with environmentally induced variation and macroevolutionary chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
80
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 104 publications
(86 citation statements)
references
References 40 publications
(82 reference statements)
6
80
0
Order By: Relevance
“…Previous studies indicated that unique morphological, physiological and genetic characters were always found in organisms from the extreme environments [ (Badyaev and Foresman, 2000) and (Rothschild and Mancinelli, 2001)]. Zhou et al (2008) concluded that hot spring seems to be one of the favorite living environments for organisms with active IS elements (Zhou et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that unique morphological, physiological and genetic characters were always found in organisms from the extreme environments [ (Badyaev and Foresman, 2000) and (Rothschild and Mancinelli, 2001)]. Zhou et al (2008) concluded that hot spring seems to be one of the favorite living environments for organisms with active IS elements (Zhou et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…(e) Environmental stress: Many authors have argued for a link between evolutionary innovation and environmental stress, defined in terms of the physiological tolerances of the organism rather than any absolute measure of environmental variability (e.g., Parsons, '93;Hoffmann and Parsons, '97;Badyaev and Foresman, 2000;Hoffman and Hercus, 2000;Nevo, 2001). Although many potential mechanisms for the stress-novelty link have been proposed, the most striking have recently come from molecular biologists.…”
Section: Mechanismsmentioning
confidence: 98%
“…Of a special theoretical and empirical interest is the question of temporal persistence of genetic covariance structure. In particular, understanding temporal constancy of genetic covariance patterns can enable us to explore mechanisms behind population divergence (Lande 1985;Price and Grant 1985;Grant and Grant 1995;Cheverud 1996;Arnold and Phillips 1999;Camara and Pigliucci 1999;Badyaev and Foresman 2000).…”
Section: Discussionmentioning
confidence: 99%
“…If genetic covariance matrix remains constant over time since divergence and genetic drift is the primary cause of divergence, we expect (1) congruency or proportionality among population matrices (Lande 1980;Lofsvold 1988;Armbruster 1991;Bjö rklund 1994;Badyaev and Foresman 2000), i.e., the morphological diversification among house finch populations should occur in the directions predicted by within-population correlation or covariance structures (Schluter 1996); and (2) concordance in patterns of divergence in covariance matrices between males and females. Alternatively, if population divergence resulted from locally distinct selection pressures, no congruence would be expected both between within-and among-population covariance structures and between divergence of male and female covariance structures (Lande 1985;Riska 1985;Zeng 1988;Arnold and Phillips 1999;Camara and Pigliucci 1999).…”
mentioning
confidence: 99%